"Arbeit und Brot": Die sozioökonomische NS-Propaganda vor 1933 - Nikolaus Kowall (Wirtschaftsdienst, 2023)
Die NSDAP kopierte nicht nur von Anfang an den Stil der Arbeiterbewegung, sondernverlagerte auch den Schwerpunkt ihrer Propaganda ab 1928 von nationalistischer Außenpolitikauf innenpolitische und soziale Fragen. Bis 1932 wurde diese Ausrichtung jedoch durchkein wirtschaftspolitisches Programm untermauert. Dies änderte sich in der Endphase derWeimarer Republik, als die NSDAP die politische Bedeutung der Massenarbeitslosigkeiterkannte und als einzige Partei frühkeynesianische Ideen aufgriff. Diese sozioökonomischeAusrichtung mag wesentlich zum Wahlerfolg vom Juli 1932 beigetragen haben, als die NSDAPdie SPD als stärkste Partei im Reichstag ablöste. – – The NSDAP not only copied the style of the labour movement from the start, but also shifted the focus of its propaganda from 1928 onward from nationalistic foreign policy to domestic and social issues. Until 1932, however, the new socio-economic focus was not underpinned by any concrete economic policy programme. This changed in the final phase of the Weimar Republic, when theNSDAP recognised the political importance of taking action against mass unemployment like no other party. Ideas for active economi policy using central bank-financed employment programmes, which the leading National Socialist Gregor Strasser adopted from early Keynesian and trade union circles, served as the programmatic basis. The topic was job creation, the slogan was "work and bread"and the explicit main opponent, the SPD, was blamed for unemployment, misery and bankruptcy. This socio-economic focus may have contributed significantly to the electoral success of the NSDAP in July 1932, when it replaced the SPD as the strongest party in theReichstag. The Nazis were able to garner more than a quarter of the workers' votes and became the strongest party - even among the workers. With this, the NSDAP turned into a people's party, which was drawn from all milieus.
Keywords: B24; N14; N44; 330